The Uncovering Cultural Capital in Indonesia's Underground Music Scene: A Discourse - Catur Surya Permana (JOMANTARA, 2022)
Underground music is considered to have a very strong context in terms of cultural capital. Pluralism and musical concepts can precipitate the ruling regime. So that it raises a reaction to freedom in voicing certain class ideologies. The role of music was finally able to represent the voices of the politicized or oppressed people overpowering, one of which occurred in the New Order. Underground music emerged as a cultural capital which Bourdieu called an artifact in dissecting the problems of the social field. The purpose of this research is to uncover the cultural capital possessed by Underground Music which creates views that open the minds and hearts of representatives of certain classes. This research is carried out by reviewing literature, musicology, and historical records of Underground music, which will be presented and dialogued with the concept of Modal theory from Bourdieu and popular music analysis from David Machin. This research tries to answer the image anxiety that emerges from the dark and loud Underground Music Scene but instead has a sacred context in the development of the socio-cultural situation in Indonesia.